The Reality of Using Professional Standards for Teachers from their Viewpoints in Public Schools in Jordan and their Attitudes toward it - Haitham Fuad Darwish (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aims to identify the reality of using professional standards for teachers from their viewpoints in schools of the Directorate of Education for the University District / Capital Governorate and their attitudes toward it. Methods: The study adopted the descriptive survey method and used the questionnaire to collect data. The questionnaire consisted of (46) items to collect data from the sample which amounted to (500) male and female teachers from the primary and secondary classes in the Directorate of Education of the University of Jordan / Capital Governorate, where teachers were asked about the professional standards. Results: The results revealed that the degree of male and female teachers' application to professional standards in Jordan is medium. They also demonstrated that primary and secondary teachers' attitudes in Jordan toward professional standards are negative. Conclusions: The study recommends increasing the number of professional development courses for teachers and not limiting them to a small number of classes in each scholastic year.